Masa crítica (2017)
In a society of consumption, like the current, in which there is a constant flow of material, I find myself continuously in the research of materials of industrial origin that stimulate my creative process. Critical Mass, is a project born from the interest for matter, its experimentation and for the forms that result when working with it. The pieces confront the viewer with a materiality that due to its multiple uses happens unnoticed in daily life, and that only when is presented to us in its no conventional forms is revealed magically like something intriguing. I'm interested in the biomorphic quality that can arise from the experimentation with this type of synthetic materials. Each work is the result of a process of intuition-action that allows the material to express in an autonomous way. The project is configured by the personal recognition of some plastic needs, as well by the exploration of material as an aesthetic category in contemporary art.--Tomado del Formato de Documento de Grado.